LEGAL PROTECTION FOR CREDITORS IN BANKRUPTCY PROCESSES REVIEWED FROM BANKRUPTCY LAW NO. 37 OF 2004 - Ihsan Hamdi Armaoyuda Siregar; Bambang Fitrianto (PT. Sinergi Legal Publisher, 2025)
Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU) is a legal framework that regulates bankruptcy procedures in Indonesia, aimed at protecting creditors' rights in cases of debtor failure to fulfill their obligations. However, the existing protection is often inadequate, especially for concurrent creditors who do not have collateral for assets. The focus of this study is to evaluate the effectiveness of UUK-PKPU in protecting creditors, especially in conditions where the debtor's assets are insufficient. The methodology used is a normative legal approach with analysis of related documents and literature. The results of the study indicate that, although bankruptcy is regulated in detail, its implementation has not been effective in providing protection to concurrent creditors. Separatist creditors are given priority through execution rights, while concurrent creditors often lose the opportunity for debt recovery due to limited assets. The actions of debtors who hide assets have also not been dealt with firmly. The research recommendations include changes to the Criminal Code to increase sanctions for criminal acts of bankruptcy, development of credit insurance products, and strengthening the role of curators in auditing shareholders, which aim to create a fairer and more effective bankruptcy system.